EUROPEAN EXPERIENCE OF PUBLIC MANAGEMENT OF INNOVATIVE DEVELOPMENT OF SMALL AND MEDIUM-SIZED BUSINESSES - Noskov, Oleksii (Public Management and Policy, 2025)
The relevance of the topic is determined by the tasks of the restoration of Ukraine and the need to determine the main directions, forms, and methods of reforms for this. The purpose of the study is to determine, based on foreign and domestic experience, the key factors of successful innovative development of the Ukrainian economy in general and small and medium-sized businesses (SMEs), in particular, during the period of martial law and reconstruction. The study’s main hypothesis is to substantiate the need for a comprehensive approach to public management of innovative development of SMEs. The research methods correspond to the complexity of the topic. The following were used: analysis and synthesis – to identify the constituent elements of the EU and member states' policies; retrospective analysis – to determine the change in priorities of Ukrainian scientists; comparative analysis – to compare public administration practices; a systemic approach – to comprehensively determine development tasks; case studies – to study successful examples and shortcomings of individual countries. During the study, a selection of empirical materials was made, regulatory documents and scientific publications of Ukrainian and foreign scientists were processed, the practice of preparing and implementing reforms for the restoration and development of SMEs was summarized, positive practices and shortcomings in choosing priorities were assessed, key tasks were identified and the experience of organizing public management of innovative development of SMEs in the EU and individual member states was systematized and summarized. It is proposed to pay more attention to the experience of Croatia and other Balkan countries, while taking into account their shortcomings. The theoretical significance of the study lies in the systematization of approaches to the problem of ensuring innovative development of SMEs. The practical significance of the study is determined by the possibility of using its results in the preparation of regulatory documents, scientific publications and textbooks. The scientific novelty lies in the conceptualization of the role of public administration in the restoration of small and medium-sized businesses (SMEs) in the post-crisis development of Ukraine and the justification of the need for a global approach, combining the specifics of national development with the implementation of European integration tasks. The author outlines the prospects for further research in defining debatable issues, including: free trade or protectionism, priority support for large or SMEs, the ratio of administrative and financial methods of influence on the innovative development of SMEs, the level of regulation: deregulation or thorough normalization of all processes. The article is empirical in nature.